The Impact of Inquiry-Based Learning (IBL) on the Expository Writing Skills of Learners in Nigeria: An Experimental Study on Improving Writing Structure and Organization - Abdulkareem, Mariam Jenrola (Journal of Foreign Language Teaching and Learning, 2000)
Background: The Nigerian English language curriculum for writing mostly encourages a teacher-centred approach whereby the teacher simply gives writing task to students and leave them to figure it out on their own. This leaves many of the students stuck and thereby losing interest in English composition. Objective: This study hereby investigates how Inquiry-Based Learning (IBL) impacts the writing performance of secondary school students in Nigeria to see if a more student-centered approach might change the students’ perspective and performance. The study specifically focuses on organization and structure in expository writing. It primarily aims to determine whether using a student-centred approach like IBL can improve students’ writing performance. Methods: A seven-week experimental study was conducted, and this involved an experimental group that was taught using IBL strategies and a control group that received traditional instruction. At the beginning of the study, each group consisted of 20 students, making the initial sample size 40. However, only 10 students from each group completed both the pre-test and post-test, which resulted in 20 valid responses. This reduction was largely because of the students’ motivation and attitudes toward the process, which affected their participation. Data collection included pre-tests and post-tests to assess students’ writing performance. Findings: The results of the experiment underscore that no significant differences were observed between the performance of the experimental and control group. While IBL did not lead to measurable improvements in students’ ability to organize and structure expository essays, the study highlights the value of active student engagement in the learning process. Conclusion: The findings suggest that the results may differ with a larger sample size and a longer period of intervention.